Evaluation of the effect of gabapentin on postoperative analgesia with epidural morphine after abdominal hysterectomy - Aryal, Diptesh; Gurung, Renu; Marhatta, Moda Nath (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Gabapentin has been used successfully as a non-opioid analgesic adjuvant for postoperative pain management. We hypothesized that the preoperative use of gabapentin prolonged the analgesic effect of epidural morphine without an increase in adverse effects of morphine. Materials & Methods: In a randomized, double blind study sixty ASA PS I and II patients undergoing abdominal hysterectomy were assigned to receive either placebo or gabapentin 1200mg 1 hour before surgery. Postoperatively, 0.125% bupivacaine with morphine 50 µg per kg body weight was used for epidural analgesia. Vital parameters, time to the first request for analgesic, visual analogue scale scoring for pain at rest and during movement, 24-hour morphine consumption, and side effects were studied. Results: The patients were comparable with respect to age, weight, ASA PS, baseline hemodynamic parameters and duration of surgery. Gabapentin significantly decreased the duration of analgesia compared to placebo (1078.26 min Vs. 303.5 min; P value <0.0001). The VAS scores at rest and during movement at 1, 2, 4, 8, 12, and 24h were significantly lower in gabapentin group. The total amount of morphine consumption in 24 h postoperatively was significantly lower in gabapentin group (1.93mg Vs. 6.30mg; P value <0.0001). The incidence of nausea and pruritus was significantly lower with gabapentin. Conclusion: Oral gabapentin 1200 mg as a premedication decreases the dose requirement of epidural morphine and postoperative pain after total abdominal hysterectomy. It also decreases the pain scores at rest and during movement significantly.